International Humanitarian Law and the Use of Starvation as a Method of Warfare: Positive Duties on the Parties to the Conflict - Nwotite, Anita (ABUAD Law Journal, 2023)
Starvation is one of the numerous humanitarian consequences following armed conflicts as a result of the obstruction in the chain of production and distribution. However, the situation becomes worrisome when starvation isemployed by the parties to a conflict as a method of warfare. This trend was obvious in a number of contemporary armed conflicts such as Russia-Ukraine war, Syrian war, Ethiopia-Tigray war, and Yemeni war, to mention but a few. These were all characterized by the destruction of objects indispensable to the survival of the civilian population and in some casethe obstruction of humanitarian access to civilians in need of humanitarian assistance. Against this background, the paper focuses on examining the rules of International Humanitarian Law regulating the use of starvation as a method of warfare, with a view to identifying the positive obligation of the parties to conflict towards strengthening these rules. The study adopted the traditional doctrinal method of legal research combined with qualitative approach. It is the finding of this paper that deliberate attacks against objects indispensable to the survival of the civilian population; and the obstruction of humanitarian access to civilians in need of humanitarian assistance are the major ways through which civilians are starved in situations of armed conflicts. To tackle this problem, the paper recommended among other things, the use of the distinctive emblems to enhance the distinction between civilian objectives and military objectives; and the facilitation of the passage relief materials particularly foodstuff for civilians in need of humanitarian assistance.